Reconstructing the gluon - Cyrol, Anton Konrad; Pawlowski, Jan M.; Rothkopf, Alexander; Wink, Nicolas (Arxiv, 2018)
We reconstruct the gluon spectral function in Landau gauge QCD from numerical data for the gluon propagator. The reconstruction relies on two novel ingredients: Firstly we derive analytically the low frequency asymptotics of the spectral function. Secondly we construct a functional basis from a careful consideration of the analytic properties of the gluon propagator in Landau gauge. This allows us to reliably capture the non-perturbative regime of the gluon spectrum. We also compare different reconstruction methods and discuss the respective systematic errors.
Gesehen am 18.12.2018